Study on the degradation pathway of benzo[a]pyrene by Bacillus sp. strain M1 - Zhang, Xiaoxue; Ning, Guohui; Qi, Mingyue; Li, Jiahui; Zhang, Xuena; Hao, Rui; Zhao, Xuefeng; Wang, Xiaomin; Yang, Zhixin (Frontiers in Microbiology, 2025)
Bacillus sp. strain M1, originally isolated from soil contaminated with polyaromatic hydrocarbons during earlier work of our group, has a strong ability to degrade benzo[a]pyrene (BaP). Here we show that the bacteria can utilize phthalic acid, protocatechuic acid, salicylic acid, catechol or gentisic acid as the sole carbon source, with utilization of 65.50–92.28% within 2 days. The metabolites formed during culture of Bacillus sp. strain M1 in mineral salt medium with BaP as the sole carbon source were detected by GC–MS. Intermediate metabolites were identified that included 4,5-dimethylphenanthrene, 9-ethyl-10-methylanthracene, 2-ethylacridine, phthalate derivatives, silylated catechol, and salicylic acid. The involvement of six relevant intracellular enzymes, namely phthalate dioxygenase, salicylate hydroxylase, catechol-1,2-dioxygenase, catechol-2,3-dioxygenase, gentisic acid dioxygenase and dehydrogenases, was demonstrated, and their activities correlated with the level of BaP degradation. Incorporating all findings, we propose a degradation pathway of BaP by strain M1 that starts with an enzymic attack of the C-9/C-10 or the C-7/C-8 bond. The pathway is summarized as BaP → cis-4,5-pyrene dihydrodiol → 4,5-dimethyl phenanthrene → 1-hydroxy-2-naphthalic acid. In addition, two new products, 9-ethyl-10-methylanthracene and 2-ethylacridine, were discovered.